Bring dying at home: What facilitates and hinders home-based end-of-life care for people living with dementia?-A systematic review and meta-ethnography protocol. - Guo Yin; Divya Sivaramakrishnan; Leah Macaden (PLoS ONE)
Background Although home-based end-of-life care is more in line with the preferences of people living with dementia, operationalizing this ideal remains challenging. Many people living with dementia are still unable to die at home or receive end-of-life care at home. This review aims to apply meta-ethnography to synthesize existing qualitative studies, to identify the facilitators and barriers of home-based end-of-life care for people living with dementia. Methods This review will use the meta-ethnography method to systematically synthesize and analyze qualitative studies. The seven stages described by Noblit and Hare (1988) will serve as the framework for this review. The systematic literature search will comprehensively cover the following databases: PubMed, MEDLINE, EMBASE, Cochrane Library, PsycINFO, CINAHL, and Web of Science. Inclusion criteria are: (A) qualitative research design; (B) participants are people living with dementia, family caregivers, or healthcare providers; (C) discussion of barriers and facilitators affecting home end-of-life care for people living with dementia; (D) original peer-reviewed studies in English. The included studies will be quality assessed using the CASP quality assessment form. The entire research process will refer to the meta-ethnography reporting guidelines (eMERGe) and the PRISMA statement to ensure the scientific and systematic nature of the results. Discussion This review will synthesize and analyze the results of different qualitative studies, transforming different perspectives through an iterative process of comparison, translation, and synthesis to generate new insights, and will form a comprehensive and insightful interpretive framework. This will promote a more comprehensive and in-depth understanding of the facilitators and barriers to the implementation of home-based end-of-life care for people living with dementia. In addition, the results of this review will guide the development and improvement of home-based end-of-life care interventions for people living with dementia, and guide policymakers and practitioners to optimize relevant policies and services.